Impact of cancer chemotherapy before ovarian cortex cryopreservation on ovarian tissue transplantation. Issue 6 (22nd May 2019) - Poirot, C; Fortin, A; Lacorte, J M; Akakpo, J P; Genestie, C; Vernant, J P; Brice, P; Morice, P; Leblanc, T; Gabarre, J; Delmer, A; Badachi, Y; et al.
Abstract: STUDY QUESTION: How efficacious is transplantation of ovarian cortex previously exposed to chemotherapy? SUMMARY ANSWER: Prior exposure to chemotherapy did not disrupt the function of cryopreserved ovarian tissue after transplantation. WHAT IS KNOWN ALREADY: Ovarian tissue cryopreservation (OTC) followed by ovarian tissue transplantation (OTT) is an efficacious technique for restoration of female fertility. At least 130 children have been born following this procedure. To date, little is known about the efficacy of OTT in patients exposed to cancer chemotherapy prior to OTC. STUDY DESIGN, SIZE, DURATION: This study evaluates the recovery of ovarian function and fertility in 31 consecutive patients who had received OTT, between 2005 and 2015. PARTICIPANTS/MATERIALS, SETTING, METHODS: Thirty one patients, wanting children, were transplanted with autologous ovarian cortex, among which 22 patients (71%) had been exposed to chemotherapy before OTC. Recovery of ovarian function was considered total once menstruation occurred. Ovarian function recovery (OFR), ovarian graft survival, and incidence of pregnancy were related to previous chemotherapy exposure, type of chemotherapy and graft characteristics (number of grafted fragments and follicular density). MAIN RESULTS AND ROLE OF CHANCE: The amount of ovarian tissue collected was the only parameter to show any significant change between patients with versus without previous chemotherapy. At 1 year after OTT, the cumulative incidence of OFR was 83% (93% in patients exposed to chemotherapy and 67% in others ( P  = 0.14)). A low follicular density (<0.3 foll/mm 2 ) in the transplant and a low number of grafted fragments (<16) were significantly associated with a delayed OFR. Graft survival at 2 years after OTT was 77%. It was significantly lower in patients exposed to bifunctional alkylating agents before ovarian cryopreservation and in patients with a low follicular density. The proportion of women who succeeded in having at least one live birth was 23% in the total population, 0% (0/9) in the group 'no previous chemotherapy', and 32% (7/22) in the group 'previous chemotherapy'. The cumulative incidence of pregnancy (Kaplan–Meier) at 3 years after OTT was 36% overall and 49% in case of previous chemotherapy, with no difference related to previous chemotherapy exposure. In total there were 13 pregnancies and 8 births in 7 patients. LIMITATIONS, REASONS FOR CAUTION: The pathology in the two groups of patients was not comparable. In the group of patients who had chemotherapy before OTC, there were 95% of hematological malignancies. In the group of patients who did not have chemotherapy before OTC only 1 out of 9 patients had a malignant hematological disease while 44% had some pathology affecting the ovaries. Few women are available for study and only large changes are likely to have statistical significance. WIDER IMPLICATIONS OF THE FINDINGS: These results suggest that prior cancer chemotherapy should no longer be considered a limitation to cryopreservation of ovarian tissue and current recommendations in this regard should be revised. STUDY FUNDING/COMPETING INTEREST(S): This study was supported by the Agence de la Biomédecine (France's biomedical office). There are no competing interests to report. TRIAL REGISTRATION NUMBER: NCT02184806.